Impact on Fertility After Failure of Restorative Proctocolectomy in Men and Women With Ulcerative Colitis: A 17-Year Cohort Study. Issue 6 (June 2020) - Pachler, Frederik Rønne; Bisgaard, Thue; Mark-Christensen, Anders; Toft, Gunnar; Laurberg, Søren
Abstract : BACKGROUND: Impact of restorative proctocolectomy failure on fertility has not been studied and is greatly relevant. OBJECTIVE: The purpose of this study was to evaluate the impact of restorative proctocolectomy failure on birth rate in women and men, along with in vitro fertilization incidence and success. DESIGN: This was a retrospective registry-based cohort study over 17 years. SETTINGS: Records for parenting a child were cross-linked with patient records. In women, in vitro fertilization records were cross-linked. All data were prospectively registered. PATIENTS: Patients of fertile age with ulcerative colitis between 1994 and 2010 were identified in Danish national databases. Patients with restorative proctocolectomy and restorative proctocolectomy failure were identified as subgroups. MAIN OUTCOME MEASURES: Birth rate ratios and in vitro fertilization incidence and success were measured. RESULTS: We included 11, 939 women and 13, 569 men with ulcerative colitis. A total of 711 women and 730 men had restorative proctocolectomy; 114 women and 90 men had failure. Birth rate in women with failure was significantly reduced compared with women without (birth rate ratio = 0.50 (95% CI, 0.29–0.82)). In men with failure, birth rate tended to be lower compared with men without (birth rate ratio = 0.74 (95% CI, 0.51–1.05)). In vitro fertilization incidence was similar with and without failure (HRs adjusted for age at start of follow-up = 0.98 (95% CI, 0.58–1.67]). In vitro fertilization success was significantly lower with failure compared with ulcerative colitis (OR adjusted for age at start of follow-up = 0.36 (95% CI, 0.4–0.92)). LIMITATIONS: Information on patients leading up to restorative proctocolectomy failure is lacking. Failure patients may have had children during a period with pouch function. Therefore, the impact of failure may be underestimated. CONCLUSIONS: Restorative proctocolectomy failure impairs birth rate, primarily in women. Although in vitro fertilization incidence is similar in women with and without failure, the likelihood of giving birth after in vitro fertilization is reduced. See Video Abstract at http://links.lww.com/DCR/B202 . Impacto Sobre la Fertilidad Después del Fracaso de la Proctocolectomía Restauradora en Hombres y Mujeres con Colitis Ulcerosa: Un Estudio de Cohorte de 17 Años: ANTECEDENTES: No se ha estudiado el impacto de la falla de la proctocolectomía restauradora en la fertilidad y es muy relevante. OBJETIVO: Evaluar el impacto del fracaso de la proctocolectomía restauradora en la tasa de natalidad en mujeres y hombres, junto con la incidencia y el éxito de la fertilización in vitro. DISEÑO: Estudio de cohorte retrospectivo basado en el registro de más de 17 años. AJUSTES: Los registros de crianza de un niño se cruzaron con los registros de pacientes. En las mujeres, los registros de fertilización in vitro se cruzarón. Todos los datos se regitraron de forma prospectiva. PACIENTES: Los pacientes de edad fértil con colitis ulcerosa entre 1994-2010 fueron identificados en las bases de datos nacionales danesas. Los pacientes con proctocolectomía restauradora y fracaso de la proctocolectomía restauradora se identificaron como subgrupos. PRINCIPALES MEDIDAS DE RESULTADO: Tasas de natalidad e incidencia y éxito de la fertilización in vitro. RESULTADOS: Se incluyeron 11939 mujeres y 13569 hombres con colitis ulcerosa. 711 mujeres y 730 hombres tuvieron proctocolectomía restauradora; 114 mujeres y 90 hombres tuvieron fracaso. La tasa de natalidad en las mujeres con fracaso se redujo significativamente en comparación con las mujeres sin fracaso (tasa de natalidad: 0, 50; IC del 95% [0, 29; 0, 82]). En los hombres con fracaso, la tasa de natalidad tendió a ser más baja en comparación con los hombres sin fracaso (tasa de natalidad: 0, 74; IC del 95% [0, 51; 1, 05]). La incidencia de fertilización in vitro fue similar con y sin falla (aHR: 0.98, IC 95% [0.58; 1.67]). El éxito de la fertilización in vitro fue significativamente menor con el fracaso en comparación con la colitis ulcerosa (aOR: 0.36 IC 95% [0.4; 0.92]). LIMITACIONES: Falta información sobre los pacientes que conducen al fracaso de la proctocolectomía restauradora. Los pacientes con fracaso pueden haber tenido hijos durante un período con función de bolsa. Por lo tanto, el impacto del fracaso puede ser subestimado. CONCLUSIÓN: El fracaso de la proctocolectomía restauradora afecta la tasa de natalidad, principalmente en mujeres. Aunque la incidencia de la fertilización in vitro es similar en las mujeres con y sin fracaso, la probabilidad de dar a luz después de la fertilización in vitro se reduce. Consulte Video Resumen en http://links.lww.com/DCR/B202 . (Traducción—Dr Gonzalo Hagerman)